MODERN TECHNOLOGIES AND METHODS FOR EMPLOYEE EVALUATION: PRACTICAL OPPORTUNITIES AND CONTEMPORARY CHALLENGES - Ma’mur Shukhratov; Jasur Baxodirov (Research Focus International Scientific Journal, 2025)
This article provides an in-depth analysis of employee evaluation systems, highlighting their importance for effective organizational management. Such systems not only support managerial decision-making but also contribute to increased labor productivity. The authors examine the principal criteria for comprehensive employee performance evaluation and analyze methods to improve efficiency across various work environments. The study identifies the strengths and weaknesses of contemporary assessment approaches, considering evaluation mechanisms appropriate for different job levels. The findings indicate that relying solely on traditional methods is insufficient; special attention is given to the implementation of Key Performance Indicators (KPIs). Furthermore, the article discusses challenges associated with KPI systems and offers recommendations for their more effective integration.